Sediment spiking and equilibration procedures to achieve partitioning of uranium similar to contamination in tropical wetlands near a mine site. (15th February 2022) - Harford, Andrew J.; Simpson, Stuart L.; Humphrey, Christopher L.; Parry, David L.; Kumar, Anu; Chandler, Lisa; Stauber, Jennifer L.; van Dam, Rick A.
Abstract: The derivation of sediment quality guideline values (SQGVs) presents significant challenges. Arguably the most important challenge is to conduct toxicity tests using contaminated sediments with physico-chemistry that represents real-world scenarios. We used a novel metal spiking method for an experiment that ultimately aims to derive a uranium SQGV. Two pilot studies were conducted to inform the final spiking design, i.e. percolating a uranyl sulfate solution through natural wetland sediments. An initial pilot study that used extended mixing equilibration phases produced hardened sediments not representative of natural sediments. A subsequent percolation method produced sediment with similar texture to natural sediment and was used as the method for spiking the sediments. The range of total recoverable uranium (TR-U) concentrations achieved was 8–3200 mg/kg. This reflected the concentrations found in natural wetlands and water management ponds found on a uranium mine site and was above natural levels. Dilute-acid extractable uranium (AE-U) concentrations were >80% of total concentrations, indicating that much of the uranium in the spiked sediment was labile and potentially bioavailable. The portion of TR-U extractable as AE-U was similar at the start and end of the 4.5-month field-deployment. Porewater uranium (PW–U) analyses indicated that partition coefficients (Kd) were 2000–20, 000 L/kg, and PW-U was greater in post- than pre-field-deployed samples when TR-U was ≤1500 mg/kg, indicating the binding became weaker during the field-deployment period. At higher spiked-U concentrations, the PW-U was lower post-field-deployment. Comparing the physico-chemical data of the spiked sediments with environmental monitoring data from sediments in the vicinity of a uranium mining operation indicated that they were representative of sediments contaminated by mining and that the U-spiked sediments had a clear U concentration gradient. This confirmed the suitability of the spiking procedure for preparing sediments that were suitable for deriving a SQGV for uranium. Graphical abstract: Image 1 Highlights: There are no Sediment Quality Guidelines for Uranium, which protect aquatic ecosystems. The artificial spiking of sediments is challenging, and metals partitioning needs to be known. We trialed various sediment spiking methods and compared to sediments near a mine site. The spiked sediments were representative of contaminated sediments near the mine. The sediments had a U contamination gradient that was suitable for toxicity testing.